2012
DOI: 10.1590/s0100-879x2012007500111
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies of pirarubicin-loaded SWNT for the treatment of bladder cancer

Abstract: Intravesical chemotherapy is an important part of the treatment for superficial bladder cancer. However, the response to it is limited and its side effects are extensive. Functional single-walled carbon nanotubes (SWNT) have shown promise for tumor-targeted accumulation and low toxicity. In the present study, we performed in vivo and in vitro investigations to determine whether SWNT-based drug delivery could induce high tumor depression in rat bladder cancer and could decrease the side effects of pirarubicin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Epirubicin-loaded poly(ethyl-2-cyanoacrylate) nanoparticles have been studied in vitro and demonstrate increased cytotoxicity, but also increased drug concentrations within superficial tissue of treated porcine bladders [27]. In addition to nanoparticles, single-walled carbon nanotubes (each ~150 nm in length) decorated with PEG and loaded them with pirarubicin demonstrated much higher drug retention within the bladder than free pirarubicin in a mouse model, and histologic examination of treated bladder tumors showed higher apoptosis rates of apoptosis than free drug [47]. …”
Section: Nonmyoinvasive Bladder Cancermentioning
confidence: 99%
“…Epirubicin-loaded poly(ethyl-2-cyanoacrylate) nanoparticles have been studied in vitro and demonstrate increased cytotoxicity, but also increased drug concentrations within superficial tissue of treated porcine bladders [27]. In addition to nanoparticles, single-walled carbon nanotubes (each ~150 nm in length) decorated with PEG and loaded them with pirarubicin demonstrated much higher drug retention within the bladder than free pirarubicin in a mouse model, and histologic examination of treated bladder tumors showed higher apoptosis rates of apoptosis than free drug [47]. …”
Section: Nonmyoinvasive Bladder Cancermentioning
confidence: 99%
“…Several studies have shown the degree of influence of nanoparticles size on its penetration in tumor (Huo, 2013;Hrkach et al, 2012). The size also affects the systematic distribution and the clearance of nanoparticles, smaller sizes favor excretion in the kidneys (5.5 nm cut off renal filtration) (Choi et al, 2007) and larger sizes favor metabolism by the liver (50-100 nm cut off liver filtration), or are leakage at the inter-endothelial splenic cell slits(400-500 nm) (Moghimi et al, 1991). Consequently, the size of the drug delivery nanoparticles must be between 10-100nm.…”
Section: General Characteristics Of Nanoparticles With Therapeutic Spmentioning
confidence: 99%
“…Drug vectorization by covalent bond is achieved using spacer agents as ethylenediamine, cisteamine, diaminotriethylene glycol, etc to link the drug directly to the NTC (Wu et al, 2009, Bhirde et al, 2009, Samori 2010, or the drug can be link to functionalizing agent by esterification (Chen et al, 2012, Marega et al, 2011.…”
Section: Drug Vectorization In Nanotubesmentioning
confidence: 99%
“…5 Several different types of NPs have already been designed for treatment of bladder cancer, mostly to deliver chemotherapeutic drugs and other therapeutic and imaging molecules. [6][7][8][9][10][11] For targeted delivery to bladder cancer cells, different ligands have been used, such as lectins 12,13 or transferrin.…”
Section: Introductionmentioning
confidence: 99%
“…15 In vivo studies demonstrated that complexation or encapsulation of cytotoxic agents into different NPs (liposomes, polymeric NPs) can improve the efficiency of intravesical therapy. [6][7][8][9][10][11]16 Moreover, some NP formulations are already in preclinical and clinical studies. 17 Furthermore, in a recent study we have shown enhanced uptake of anionic polyacrylic acid (PAA) coated…”
Section: Introductionmentioning
confidence: 99%